Roman noir et drapeau noir: Didier Daeninckx and the libertarian legacy. (2nd April 2016) - Hurcombe, Martin
Abstract: The crime novelist Didier Daeninckx originally established himself as an author of historical crime fiction. His1984 novel, Meurtres pour mémoire, in particular challenged occluded and intertwined memories of the Occupation and the Algerian War of Independence. Since then, and through his subsequent writings and political activities, Daeninckx has been recognised as giving voice to a range of marginalised communities and memories. Much academic study has therefore concentrated on the recovery of the past in Daeninckx's fiction, approaching his work from the perspective of cultural history and memory studies, considering it a form of memory activism. This article offers a new perspective on Daeninckx's political engagement. It will examine Daeninckx's three contributions to Éditions Baleine's collaboratively authored detective series Le Poulpe : Nazis dans le métro (1996), Éthique en toc (2000) and La Route du Rom (2003). It will argue that they are informed by a memory of France's broad libertarian tradition which constitutes a hidden referent essential to understanding the formulation of the ethico-political counter-communities to which many of his characters (and his ideal, implied reader) belong. More particularly, it will argue that these communities form the basis of a new model of political engagement beyond party, state and class, suggesting not only the persistence but also the adaptability of libertarian thinking in Daeninckx's work and the French roman noir .